2019
DOI: 10.1038/s41598-019-46627-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of action of the trace amines octopamine, synephrine and tyramine on the porcine coronary and mesenteric artery

Abstract: Trace amines such as p- tyramine, p- octopamine and p- synephrine are found in low concentrations in animals and plants. Consumption of pre-workout supplements containing these plant-derived amines has been associated with cardiovascular side effects. The aim of this study was to determine the mechanisms of action of these trace amines on porcine isolated coronary and mesenteric arteries. Noradrenaline caused contraction of mesenteric arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A molecule related to octopamine (N-trans-feruloyloctopamine) shows anti-steatohepatitis properties in a model of non-alcoholic steatohepatitis (22). It has been reported that octopamine increases many hemocyte functions, such as phagocytosis, and these changes would tend to mitigate the decline in immunity due to the loss of molecular resources (23).…”
Section: Discussionmentioning
confidence: 99%
“…A molecule related to octopamine (N-trans-feruloyloctopamine) shows anti-steatohepatitis properties in a model of non-alcoholic steatohepatitis (22). It has been reported that octopamine increases many hemocyte functions, such as phagocytosis, and these changes would tend to mitigate the decline in immunity due to the loss of molecular resources (23).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an increase in systolic blood pressure, following a high ingestion of tyramine, is known as the “tyramine pressor response” [ 48 ]. Some results suggest that the indirect sympathomimetic effects played by trace amines are not their only mechanisms of action in the vascular system, since they can interact with other receptors [ 49 ]. Evidence has been shown that trace amines, particularly tyramine, β-phenylethylamine and octopamine, act directly on α1- adrenoreceptors, generating different responses based on the vessel evaluated.…”
Section: Trace Aminesmentioning
confidence: 99%
“…Tyramine and β-phenylethylamine are also able to promote a contractive response in guinea pig and rat isolated gut preparations, quite the opposite to what occurs in the presence of sympathomimetic amines [ 50 ]. Research carried out using a high concentration of an antagonist of TAAR1, called EPPTB (RO-5212773), has shown a reduction in the vasocontractile response in the porcine coronary artery [ 49 ]. Additionally, tyramine and β-phenylethylamine exhibit a partial antagonism at β1 and β2 adrenoceptors, while octopamine has shown a partial β1 agonism and a partial orthosteric antagonist in β2 adrenoceptors [ 35 ].…”
Section: Trace Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Citrus aurantium L. (Bitter orange) belongs to the Rutaceae family and has been incorporated in supplements as an ergogenic aid or a purported natural weight-loss agent. 2 The primary alkaloid, (±)-p-synephrine, is an isomer of the α 1 -adrenergic receptor agonist, phenylephrine (Figure 1) and vascular smooth muscle contraction 3 and promotes thermogenesis by stimulating β 3 -adrenoceptors. 4 The World Anti-Doping Agency (WADA) has listed synephrine and all optical isomers of synephrine in the monitoring programme, whereas other related compounds such as methylsynephrine (oxilofrine) and octopamine are prohibited in-competition.…”
Section: Introductionmentioning
confidence: 99%